Development of Numaze Media Based on Natural Materials to Improve The Concentration of Children With Autism - Ruyanah, Ruyanah; Puridawaty, Brigita (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to develop NuMaze media at PAUD institutions in Merauke District in improving the concentration skills of autistic children. The development method used is the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The research location was conducted at PAUD institutions in Merauke District involving four autistic children from four PAUD institutions as samples in the study. Data were obtained through interviews, observations, expert validity tests, and feasibility and effectiveness tests in the field. The results of the study showed that the assessment of validators by PAUD curriculum and learning experts, the development of children with special needs, and media development showed that NuMaze media was feasible to use, with an average score of 84% (Very Good Category). The results of the study provide implications that NuMaze media can be an effective reference in improving the concentration skills of autistic children.